2021
DOI: 10.3390/molecules26195817
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Minute Analysis of Lactate from a Single Blood Drop Using Capillary Electrophoresis with Contactless Conductivity Detection in Monitoring of Athlete Performance

Abstract: A simple and fast method for the analysis of lactate from a single drop of blood was developed. The finger-prick whole blood sample (10 µL) was diluted (1:20) with a 7% (w/v) solution of [tris(hydroxymethyl)methylamino] propanesulfonic acid and applied to a blood plasma separation device. The device accommodates a membrane sandwich composed of an asymmetric polysulfone membrane and a supporting textile membrane that allows the collection of blood plasma into a narrow glass capillary in less than 20 s. Separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Therefore, the determination formate in blood and urinary oxalate and citrate is very important for diagnosis and management of diseases. CE-C 4 D has been demonstrated as a satisfactory method for the determination of various types of small organic ions, such as oxalate, citrate, [77], lactate [78][79][80], lactate and pyruvate [81,82], formate [83][84][85], oxalate, formate, and glycolate [86], and fluoroacetate [87]. The analyses of organic acids such as γ-hydroxybutyric acid in urine and serum [88], valproic acid (VPA) [89], organic acids in urine [90], uric acid in plasma and human urine [91], Ghydroxybutyric acid, ibotenic acid, and psilocybin in saliva [92], and urinary ethylmalonic acid [93] employing CE-C 4 D were also reported.…”
Section: Organic Ions and Low Molecular Organic Acidsmentioning
confidence: 99%
“…Therefore, the determination formate in blood and urinary oxalate and citrate is very important for diagnosis and management of diseases. CE-C 4 D has been demonstrated as a satisfactory method for the determination of various types of small organic ions, such as oxalate, citrate, [77], lactate [78][79][80], lactate and pyruvate [81,82], formate [83][84][85], oxalate, formate, and glycolate [86], and fluoroacetate [87]. The analyses of organic acids such as γ-hydroxybutyric acid in urine and serum [88], valproic acid (VPA) [89], organic acids in urine [90], uric acid in plasma and human urine [91], Ghydroxybutyric acid, ibotenic acid, and psilocybin in saliva [92], and urinary ethylmalonic acid [93] employing CE-C 4 D were also reported.…”
Section: Organic Ions and Low Molecular Organic Acidsmentioning
confidence: 99%
“…Lactate has been determined in biological samples mostly using enzymatic-and nonenzymatic-based sensors [12,[14][15][16][17][18]. However, other methods, such as CE [19][20][21][22], HPLC [23], and spectroscopy [24,25], can also be used. The determination of lactate in sweat has recently been extensively explored using colorimetric [26][27][28][29] and wearable electrochemical sensors [6,8,17,18,30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CE consumes small amounts of samples and reagents and generates low volumes of waste, making it environmental friendly. Therefore, several studies can be found in the literature regarding lactate determination by CE in various samples, particularly in biological matrices such as vitreous humor [19], exhaled breath condensate [22], plasma [21], and blood [20]. The application of CE for sweat analysis has also been explored [31][32][33][34][35][36][37][38][39][40], particularly for chloride determination aiming to diagnose cystic fibrosis [31-33, 35, 31, 38].…”
Section: Introductionmentioning
confidence: 99%